Enhancement of oil content in safflower (Carthamus tinctorious L.): Enhancement of oil content in safflower (Carthamus tinctorious L.) - RAJEEV SHRIVASTAVA; YENKHOM LINTHOI; SURBHI VERMA; VAGEESHWARI; ASMITA PILLAI (Journal of Oilseeds Research, 2023)
A systematic breeding approach is applied to increase the oil content in safflower lines by crossing between elite GMU lines and Mexican lines. The range of oil content in elite GMU parental lines were 33-35% were as in Mexican lines the average oil content was 39%. The crosses were made, through transgressive segregation the oil content in F5-F6 generations was achieved up to 42%.